Family Knowledge in Post-Stroke Pressure Wound Prevention in the Working Area of the Balowerti Health Center, Kediri - Didik Susetiyanto Atmojo (Fakultas Kedokteran, 2020)
The ability of families to provide care for family members after stroke as a rehabilitation effort based on family knowledge in caring for family members with post-stroke, especially in preventing pressure sores. One of the duties of the family is to provide care to family members who are sick. This means that the family has an important role in providing post-stroke family members and care associated with community nurses. With families who do not have the knowledge and ability to care for family members after stroke on new problems, one of which is suffering related to many problems for post-stroke patients. This study aims to determine the level of family knowledge on the prevention of post-stroke pressure sores. This research is a quantitative research with descriptive methods. The research was conducted in the working area of the Balowerti Health Center, Kediri . The study was conducted on 15 post-stroke patients. Data collection using total sampling technique. The research instrument used a questionnaire. Data were analyzed univariately in the form of a frequency distribution. The results of the study showed majority of the respondent were male and majority age were 60, the level of family knowledge about the prevention of post-stroke pressure sores is very low, this will increase the risk of pressure sore while the patient is treated at homeKeywords: Family Knowledge, pressure Sore, Post Stroke